Gender & caste - Rao, Anupama (Issues in contemporary Indian feminism (London, England), 2006)
This book brings together the writing of prominent Indian academics and activists as they debate the issue in the context of Indian culture, society and politics, and explores the theoretical foundations of feminism in India. The inevitability of the association with western feminism, the status of women in colonial and independent India, and the more recent challenges to Indian feminism posed by the tide of globalization and the upsurge of the Hindu Right in Indian politics are discussed at length." "Bridging the academic/activist, personal/political and local/global divides, this collection of feminist writing shows how the movement is part of a larger project of consolidating the liberal values of secularism and democracy. It deepens our understanding of why, despite the existence of legal and constitutional rights to prevent discrimination, women are subject to oppressive practices like dowry."-